Analisis komparatif kinerja lalu lintas berdasarkan pedoman kapasitas jalan indonesia 2023 dan simulasi Vissim di Persimpangan Serdang - Muhammad Oka Mahendra; Robinson Martianus Silalahi (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
This study evaluates the operational performance of Serdang Intersection, an unsignalized three-leg junction located in a commercial area connecting Serang–Cilegon Road and Waringinkurung Road. The assessment combines analytical procedures from the Indonesian Highway Capacity Manual 2023 and microsimulation modelling using PTV Vissim software. Analysis of current conditions shows a traffic flow of 3206 passenger car units per hour, a degree of saturation of 0.75, an average delay of 12.75 seconds per passenger car unit, and a queue probability ranging from 23 percent to 46 percent, corresponding to level of service B. Projections for 2033 indicate that traffic flow will increase to 4602 passenger car units per hour, the degree of saturation will exceed capacity at 1.08, average delay will rise to 23.80 seconds per passenger car unit, and queue probability will reach 47 percent to 94 percent, resulting in level of service D. These findings underscore the urgency of infrastructure interventions such as intersection geometry optimization, priority lane adjustments, and the installation of traffic signals to mitigate congestion risks. The study demonstrates the effectiveness of integrating the Indonesian Highway Capacity Manual 2023 with microsimulation modelling using PTV Vissim (Planning Transport Traffic-Traffic in Cities Simulation Model) in comprehensively forecasting traffic performance, and it offers strategic recommendations for urban planners and policymakers.